2019
DOI: 10.1016/j.celrep.2019.06.081
|View full text |Cite
|
Sign up to set email alerts
|

The Hsp70 Chaperone System Stabilizes a Thermo-sensitive Subproteome in E. coli

Abstract: Highlights d Acute heat stress causes unfolding of a thermo-sensitive subproteome in E. coli d DnaK (Hsp70) markedly stabilizes most thermo-sensitive proteins d Numerous essential ribosomal proteins are conformationally stabilized by DnaK d Other DnaK-stabilized proteins tend to be large, multidomain, and hetero-oligomeric SUMMARYStress-inducible molecular chaperones have essential roles in maintaining protein homeostasis, but the extent to which they affect overall proteome stability remains unclear. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 64 publications
2
37
0
Order By: Relevance
“…The addition of copper disturbs protein homeostasis in cells with oxidative stress [24,26]. A common consequence in E. coli cells would be the accumulation of protein aggregates [20][21][22][23]. Therefore, we hypothesized that protein aggregation might somehow be involved in the upregulation of IbpA under the non-heat stressed conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of copper disturbs protein homeostasis in cells with oxidative stress [24,26]. A common consequence in E. coli cells would be the accumulation of protein aggregates [20][21][22][23]. Therefore, we hypothesized that protein aggregation might somehow be involved in the upregulation of IbpA under the non-heat stressed conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Although the thermometer in the mRNA (RNAT) and the transcriptional control by σ 32 are known mechanisms to upregulate the expression of IbpA, previous studies have reported that IbpA expression is also upregulated under non-heat stressed conditions, such as in the dnaKJ deletion strain or upon copper stress [22][23][24]. The absence of DnaK/DnaJ leads to the production of protein aggregates [22,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of structural homologues that differ in their chaperone dependence clearly indicates that the protein fold alone is in general not a stringent requirement for chaperone interaction (18,26,32). Comparative analyses of homologous proteins thus allow to delineate any trade-offs within alternate sequences that fold into the same native protein structures.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the determinants of specificity and selectivity of ribosomeassociated chaperones is of particular interest as they are directly coupled to the sequence de-terminants of de novo protein folding in the cell (21,31). Importantly, the integration of protein structures into chaperone interaction maps has highlighted that the structural fold of proteins alone is generally not a determining factor of chaperone interaction (18,26,32). Thus, through tremendous progress on understanding chaperone action and interaction, it has also become increasingly clear that not a single feature but rather the complex interplay of multiple protein characteristics determines their interaction with chaperones.…”
Section: Introductionmentioning
confidence: 99%